Predictive role of plasmatic biomarkers in advanced non-small cell lung cancer treated by nivolumab - Costantini, Adrien (Oncoimmunology, 2018)
Immune checkpoint inhibitors, as nivolumab, are used in advanced non-small cell lung cancer (NSCLC). However, no associated biomarker is validated in clinical practice with this drug. We investigated herein immune-related blood markers in patients with advanced NSCLC treated with nivolumab. Plasma of 43 consecutive patients were prospectively collected at time of the diagnosis of cancer, at the initiation of nivolumab and at the first tumour evaluation (2 months). Concentrations of PD-L1 (sPD-L1), soluble PD-L2 (sPD-L2), Interleukine-2 (sIl-2), Interferon-gamma (sIFN-γ), and Granzyme B (sGranB) were quantified by ELISA. Cell free RNA was quantified by Reverse Transcriptase -PCR), and plasmatic microRNAs (miRNAs) were evaluated by targeted sequencing. Expression of PD-L1 on tumour biopsies was performed by immunohistochemistry using E13LN. High sPD-L1 at 2 months and increase of sPD-L1 concentrations were associated with poor response and absence of clinical benefit (nivolumab treatment less than 6 months). The variation of sPD-L1 concentrations were confirmed by RNA quantification. sPD-L1 concentrations were not correlated with PD-L1 expression on corresponding tumour samples. Low sGranB at nivolumab initiation was also associated with poor response. High sPD-L1 and low sGranB were associated with poor progression-free survival (PFS) and overall survival (OS). Low sPD-L2, low sIl-2 and high sIFN-γ were associated with grade 3–4 toxicities. Finally, miRNA screening showed that patients with clinical benefit (n = 9) had down-expression of miRNA-320b and -375 compared to patients with early progression at 2 months (n = 9). In conclusion, our results highlight the interest of circulating biomarkers in patients treated with nivolumab.